FURNISHING ENGLISH STUDENTS’ PROFICIENCY FOR BEING PUBLIC SPEAKER TO MULTILINGUAL SOCIETY AT EDUCATIONAL MAJOR - Hepy Charli; Hayati Syafri (Universitas Negeri Padang, 2016)
The students of English Education Major is guided to be a teacher later on. Nevertheless, not all these students want to be a teacher. Moreover, the chance to be a teacher is more limited and test to be a teacher is getting difficult. Consequently, students want to work in other fields that is still related to their major. Become a public speaker is one option besides being a teacher because this occupation still in line with the teacher but stand in different field. Good English profiency is required to be a good public speaker in multilingual society. English for Occupational Purpose(EOP) can be used to fulfill the requirement by using the appropriate module. This module is purposed to furnish English students’proficiency for being a public speaker. Then, the module consist varieties, description and the qualification which is needed for each public speaker area. Through this module the students is guided and is trained to be a good public speaker to multilingual society by some simulations. Briefly, this module will help the students in enhancing their profiency and it can make them entry occupation in public speaking confidently.